Exploring the Homoeopathic Use of Allium Cepa: A Narrative Review. - Bhimrao Shinde, Shivani; Shalbidre, Archana; Jagtap, Suresh; Mukherjee, Anupam; Umesh Ghate, Varsha (Journal of Neonatal Surgery, 2025)
Background: Allium cepa (onion) is a widely cultivated plant with significant medicinal properties. It is commonly used in homeopathy and complementary medicine for its antibacterial, antioxidant, anti-inflammatory, respiratory, and anticancer effects. Bioactive compounds such as flavonoids, sulfur compounds, and polyphenols contribute to its pharmacological benefits Objective: This narrative review aims to evaluate the therapeutic applications of Allium cepa in Homoeopathic and alternative medicine Methods: A literature search was conducted using databases including Scopus, Web of Science, PubMed, Science Direct, Research gate and Google Scholar. The review selected studies from 1953 to 2024 that focused on the medicinal and Homoeopathic applications of Allium cepa. Inclusion criteria included peer-reviewed studies discussing its pharmacological effects, while non-English articles, studies focusing on culinary uses, and those lacking primary data were excluded. Results: A total of 14 papers were assessed for phytochemical and 10 articles for therapeutic value Allium cepa extracts have antimicrobial properties, particularly against Staphylococcus aureus and Aspergillus niger. They also have antioxidant properties, helping to mitigate oxidative stress in metabolic disorders like diabetes and obesity. Homoeopathic Allium cepa effectively manages allergic rhinitis, URTI, and asthma, improving patient outcomes. In vitro and in vivo studies show that Allium cepa extracts induce apoptosis, inhibit cell proliferation, and modulate gene expression in cancer cells. Conclusion: Allium cepa demonstrates significant therapeutic potential, particularly in Homoeopathic and alternative medicine. However, further large-scale clinical trials and standardized formulations are required to validate its efficacy.